(untitled) (Research, Society and Development, 2021)
Objective: To analyze the perception of health professionals about the vulnerabilities of indigenous peoples facing COVID-19, as well as to identify strategies to minimize them. Methods: This was a quantitative descriptive study, developed after the analysis of questionnaires to evaluate the knowledge and referred behavior of these peoples from the perspective of professionals that provide these services directly. The data presented were run by the software IRAMUTEQ with statistical analysis on the text corpus and words. The Descending Hierarchical Classification was applied, in which the words were agglomerated into classes and the data interpreted for subsequent discussion. Results: Three categories were presented: Physical structure and Personal Protective Equipment (PPE) used during care of indigenous people; Health promotion actions and prevention of diseases related to COVID-19 in the villages and the perception of indigenous people about the coronavirus from the perspective of health care professionals. The categories were elaborated according to the frequency of the words mentioned in the interviews with the professionals, according to the Descending Hierarchical Classification (CHD). Final considerations: It was noted the commitment of health professionals in advising the indigenous people, as well as in spreading information and preventive measures against coronavirus. Despite the challenges presented, such as resistance and cultural habits, there were major changes that contributed to health promotion strategies and disease prevention.